2017
DOI: 10.1111/acel.12595
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans orthologs of human genes differentially expressed with age are enriched for determinants of longevity

Abstract: SummaryWe report a systematic RNAi longevity screen of 82 Caenorhabditis elegans genes selected based on orthology to human genes differentially expressed with age. We find substantial enrichment in genes for which knockdown increased lifespan. This enrichment is markedly higher than published genomewide longevity screens in C. elegans and similar to screens that preselected candidates based on longevity‐correlated metrics (e.g., stress resistance). Of the 50 genes that affected lifespan, 46 were previously un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 47 publications
4
43
1
1
Order By: Relevance
“…Despite these similarities, previous studies that have investigated transcriptomic signatures of ageing have identified only few genes that show a conserved transcriptional regulation across species 7 11 . In consequence, even though a number of ageing-associated transcriptomic changes have been linked to lifespan 10 , 12 , 13 , the relationship between ageing-associated transcriptional changes as well as ageing-associated pathologies has remained largely unclear 8 , 14 . This is quite surprising as it has been shown that human diseases including ageing-associated pathologies are often associated with specific transcriptional signatures and that reverting these gene expression states back to their original healthy patterns can successfully point to potential treatments 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these similarities, previous studies that have investigated transcriptomic signatures of ageing have identified only few genes that show a conserved transcriptional regulation across species 7 11 . In consequence, even though a number of ageing-associated transcriptomic changes have been linked to lifespan 10 , 12 , 13 , the relationship between ageing-associated transcriptional changes as well as ageing-associated pathologies has remained largely unclear 8 , 14 . This is quite surprising as it has been shown that human diseases including ageing-associated pathologies are often associated with specific transcriptional signatures and that reverting these gene expression states back to their original healthy patterns can successfully point to potential treatments 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This pattern supports recent research suggesting that tryptophan metabolism may be an integral part of aging and longevity. High tryptophan (van der Goot and Nollen 2013) and low kynurenine (Sutphin et al 2017) have been shown to promote longevity in worms, and low tryptophan levels were associated with increased risk of mortality in marmosets (Hoffman et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…This increase has been associated with enhanced frailty in human subjects >65 years of age and predicts an increased mortality rate of individuals in their nineties (90). Additionally, meta-analysis of age-related gene expression changes in the peripheral blood of adult individuals identified the enzyme kynureninase (KYNU, Figure 1) as one of the most differentially expressed genes (91). In a large population screening analysis that included 7,074 human subjects that focused on studying bone mineralization, Apalset et al reported that the serological Kyn/Trp ratio negatively correlated with bone mineral density in the 71-74 year old age group as compared to younger individuals that were 46-49 years of age (92).…”
Section: Ido and Its Relationship To Host Agementioning
confidence: 99%